Advanced human T‐cell leukemia virus type 1 carriers and early‐stage indolent adult T‐cell leukemia‐lymphoma are indistinguishable based on CADM1 positivity in flow cytometry. Issue 5 (20th March 2015) - Kobayashi, Seiichiro; Watanabe, Eri; Ishigaki, Tomohiro; Ohno, Nobuhiro; Yuji, Koichiro; Nakano, Kazumi; Yamochi, Tadanori; Watanabe, Nobukazu; Tojo, Arinobu; Watanabe, Toshiki; Uchimaru, Kaoru
<x xml:space="preserve">Abstract</x> We previously reported that the cell adhesion molecule 1 (CADM1) versus CD7 plot in flow cytometry reflects disease progression in human T‐cell leukemia virus type 1 (HTLV‐1) infection. In CD4+ cells from peripheral blood, CADM1−CD7+ (P), CADM1+CD7dim (D) and CADM1+CD7− (N) subpopulations are observed. The D and N subpopulations increase as asymptomatic HTLV‐1 carriers (AC) progress to indolent adult T‐cell leukemia‐lymphoma (ATL) and the N subpopulation then expands in aggressive ATL. In the present study we examined whether the analysis can estimate the risk of developing ATL in advanced AC. Peripheral blood samples from AC (N = 41) and indolent ATL patients (N = 19) were analyzed by flow cytometry using the CADM1 versus CD7 plot for CD4+ cells and inverse long PCR (clonality analysis) of FACS‐sorted subpopulations. Almost all AC with a high HTLV‐1 proviral load (>4 copies/100 cells) had a CADM1+ (D + N) frequency of >10%. AC with 25% < CADM1+ ≤ 50% contained expanded clones similar to smoldering‐type ATL. In many patients in the 25% < CADM1+ ≤ 50% group, the proportion of abnormal lymphocytes was distributed around the 5% line, which divides AC and smoldering‐type ATL in Shimoyama's classification. In conclusion, the CADM1 versus CD7 plot is useful for selection of putative high‐risk AC. The characteristics of some AC and smoldering ATL are said to be similar; however, long‐term follow up is required and the clinical outcome (e.g. rate of transformation) of these cases should be used to determine whether to include them in the same clinical category.